Can Outcomes of a Chat-Based Suicide Prevention Helpline Be Improved by Training Counselors in Motivational Interviewing? A Non-randomized Controlled Trial - Janssen, Wilco; Raak, Jeroen van; Lucht, Yannick van der; Ballegooijen, Wouter van; Mérelle, Saskia (Frontiers in Digital Health, 2022)
Objective: To examine whether the outcomes of a chat-based suicide-prevention helpline could be improved by training counsellors in motivational interviewing (MI). Methods: In a pre- and post-test design, visitors of a chat-basednsuicide prevention helpline received either the Five-Phase Model (treatment as usual [TAU]) or MI. They completed a pre- and post-chat questionnaire on several suicide-related risk factors. Linear mixed modelling was used to estimate the effect of the condition. Furthermore, the treatment proficiency of newly trained counsellors was assessed using MI-Scope. Results: A total of 756 visitors and 55 counsellors were included in this study. The visitors showed an improvement in suicidal ideation and psychological risk factors after a chat conversation. However, there were no significant differences between the MI and TAU conditions (β = 0.03, 95% CI [-0.23-0.30], p = 0.80). The treatment integrity indices showed that the counsellors mostly used MI-consistent techniques but were unable to strategically employ these techniques to evoke enough change talk. Conclusions: MI and TAU led to comparable outcomes in a chat-based suicide prevention helpline. The effectiveness of MI might improve by intensifying or improving the training of counsellors, keeping the process of engaging more concise or offering visitors multiple sessions of MI.